Cytotoxic and Antitumor Effects of Curzerene from Curcuma longa - Wang, Youdi; Li, Jiahong; Guo, Jiquan; Wang, Qiyou; Zhu, Shuguang; Gao, Siyuan; Yang, Chen; Wei, Min; Pan, Xuediao; Zhu, Wei; Ding, Dongmei; Gao, Ruiping; et al. (Planta medica, 2017)
Curzerene is a sesquiterpene and component used in oriental medicine. It was originally isolated from the traditional Chinese herbal medicine rhizomes. In this study, anticancer activity of curzerene was examined in both and models. The result of the MTT assay showed that curzerene exhibited antiproliferative effects in SPC-A1 human lung adenocarcinoma cells in a time-dependent and dose-dependent manner. The anticancer IC s were 403.8, 154.8, and 47.0 µM for 24, 48, and 72 hours, respectively. The flow cytometry analysis indicated curzerene arrested the cells in the G2/M cell cycle and promoted or induced apoptosis of SPC-A1 cells. The percentage of cells arrested in the G2/M phase increased from 9.26 % in the control group cells to 17.57 % in the cells treated with the highest dose (100 µM) of curzerene. Western blot and RT-PCR analysis demonstrated that curzerene induced the downregulation of GSTA1 protein and mRNA expressions in SPC-A1 cells. Tumor growth was significantly inhibited in SPC-A1 cell-bearing nude mice by using curzerene (135 mg/kg daily), meanwhile, curzerene did not significantly affect body mass and the organs of the mice, which may indicate that curzerene has limited toxicity and side effects . In conclusion, curzerene could inhibit the proliferation of SPC-A1 human lung adenocarcinoma cells line in both and models. Focusing on its relationship with GSTA1, curzerene could induce the downregulation of GSTA1 protein and mRNA expressions in SPC-A1 cells. Curzerene might be used as an anti-lung adenocarcinoma drug candidate compound for further development.